2015
DOI: 10.1016/j.jconrel.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polymer backbone chemistry on the induction of the accelerated blood clearance in polymer modified liposomes

Abstract: A variety of water-soluble polymers, when attached to a liposome, substantially increase liposome circulation half-life in animals. However, in certain conditions, liposomes modified with the most widely used polymer, polyethylene glycol (PEG), induce an IgM response resulting in an accelerated blood clearance (ABC) of the liposome upon the second injection. Modification of liposomes with other water-soluble polymers: HPMA (poly[N-(2-hydroxypropyl) methacrylamide]), PVP (poly(vinylpyrrolidone)), PMOX (poly(2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(108 citation statements)
references
References 46 publications
2
101
1
4
Order By: Relevance
“…Only very little mild and scattered tubular damage was observed in POx/PTX samples (see supplementary information for a more detailed analysis). Overall, our results reinforce the excellent biocompatibility profile of POx reported previously [2233]. …”
Section: Resultssupporting
confidence: 92%
“…Only very little mild and scattered tubular damage was observed in POx/PTX samples (see supplementary information for a more detailed analysis). Overall, our results reinforce the excellent biocompatibility profile of POx reported previously [2233]. …”
Section: Resultssupporting
confidence: 92%
“…They were also able to demonstrate for the first time that HPMA-modification did not cause an ABC effect, whereas PMOX-modified liposomes were rapidly cleared with the second dose in rats. They confirmed that PMOX-modified liposomes induced an IgM response in rats with one dose, similar to PEG-modified liposomes [119]. This work suggests that alternatives such as HPMA or PVP deserve further consideration as polymer coatings to improve the circulation time of liposomes.…”
Section: Nanoparticle Pegylation For Improved Systemic Deliverymentioning
confidence: 64%
“…Also to be considered, hyperbranched PG has been observed to slightly increase blood viscosity in vivo , which has been shown to cause a variety of physiological side effects [118]. To compare the potential of several different PEG alternatives as surface modifiers to increase circulation time and reduce the ABC effect, Kiersted and coworkers synthesized a panel of polymer diacyl chain lipids of similar MW and polydispersity to incorporate into liposomes [119]. They evaluated liposomes ~100 nm in size containing lipids modified with PEG, HPMA, poly(vinylpyrrolidone) (PVP), poly(2-methyl-2-oxazoline) (PMOX), poly(N,N-dimethyl acrylamide) (PDMA), and poly(N-acryloyl morpholine) (PAcM), and compared the circulation time in mice and rats.…”
Section: Nanoparticle Pegylation For Improved Systemic Deliverymentioning
confidence: 99%
“…In addition, the unpredicted clearance times of PEGylated compounds lead to accumulation of high molecular weight compounds in the liver (Dams et al, 2000) with unknown toxicological consequences over a long period of time (Kawai, 2002). Some studies have evaluated other water-soluble polymers in order to overcome the limitations in the use of PEG (Kierstead et al, 2015). For instance, poly[N-(2-hydroxypropyl) methacrylamide] (Lammers and Ulbrich, 2010) and poly(vinylpyrrolidone) (Zelikin et al, 2007;Kierstead et al, 2015) coatings on liposomes also demonstrated the ability to extend circulation times and to avoid accelerated blood clearance although their opsonisation by plasma proteins remains poorly documented.…”
Section: Introductionmentioning
confidence: 99%